The Politics of Changing the Dutch Agri-Food System - Aarts, Noelle; Leeuwis, Cees (Journal of Political Sociology, 2023)
Tensions between farmers, government and society have recently been running high in the Netherlands. Dutch farmers are furious with the national government because of the ever-stricter nitrogen policy that is supposed to save nature in the Netherlands, in line with European directives. The current plan states that nitrogen emissions need to be reduced by 50% in 2030. The disagreement over how to tackle the nitrogen issue in the Netherlands is a deeply rooted conflict that goes back decades. In this political commentary, we analyse the conflict and argue that the solutions proposed in the public and political debate tend to ignore the systemic nature of the problem. We suggest that it is important to work towards innovation in the rules and arrangements that govern agricultural value chains to create a more conducive and enabling environment for the regional initiatives that have emerged in response to the current crisis, several of which challenge the currently dominant food system.